2013
DOI: 10.1152/jn.00869.2012
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of trkB receptors in reactive axonal sprouting and hyperexcitability after axonal injury

Abstract: Aungst S, England PM, Thompson SM. Critical role of trkB receptors in reactive axonal sprouting and hyperexcitability after axonal injury. J Neurophysiol 109: 813-824, 2013. First published November 14, 2012 doi:10.1152/jn.00869.2012.-Traumatic brain injury (TBI) causes many long-term neurological complications. Some of these conditions, such as posttraumatic epilepsy, are characterized by increased excitability that typically arises after a latent period lasting from months to years, suggesting that slow inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…However, as elaborated above for integrin receptors, additional interventions would be required to enhance the transport of TrkB into the corticospinal tract to promote substantial regeneration after spinal cord injury. In addition, it had been shown in hippocampal slice cultures that the activation state of TrkB correlates with axonal sprouting (Aungst, England & Thompson, ). The activation state of Trk receptors may therefore influence the regeneration response as well.…”
Section: The Localisation Of Other Regeneration‐associated Receptorsmentioning
confidence: 99%
“…However, as elaborated above for integrin receptors, additional interventions would be required to enhance the transport of TrkB into the corticospinal tract to promote substantial regeneration after spinal cord injury. In addition, it had been shown in hippocampal slice cultures that the activation state of TrkB correlates with axonal sprouting (Aungst, England & Thompson, ). The activation state of Trk receptors may therefore influence the regeneration response as well.…”
Section: The Localisation Of Other Regeneration‐associated Receptorsmentioning
confidence: 99%
“…We found that chronically treated TrkB‐Fc slices had fewer spontaneous APs than untreated lesioned slices. Moreover, Schaffer collateral lesion caused an increase in compound fEPSPs in area CA3, consistent with epileptiform activity and hyperexcitability, similarly to in vivo Schaffer collateral lesion (Aungst et al ., ). This change in network activity was also attenuated with TrkB‐Fc treatment.…”
Section: Discussionmentioning
confidence: 97%
“…This may have implications for post-traumatic epilepsy, as recurrent epileptic seizures are a common clinical consequence of trau-matic brain injury (Annegers et al, 1998). Others have shown that Schaffer collateral lesion can result in increased network activity after the addition of a mildly proconvulsive amount of bicuculline (0.1 lM), a GABA A receptor antagonist (Aungst et al, 2013). Moreover, evidence from in vivo models of epilepsy has shown that axonal sprouting can occur in the hippocampus after induction of status epilepticus with convulsants.…”
Section: Chronic Trkb-fc Treatment Attenuates Injury-induced Hyperexcmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies to date have utilized the TrkB F616A mutants for analysis of TrkB signalling in studies on nociception (Renn et al, 2009;Wang et al, 2009), neuromuscular function (Greising et al, 2015), hypothalamic function (Bariohay et al, 2009;Byerly et al, 2013), inhibitory circuity maturation (Vandenberg et al, 2015), spinal cord injury (Zhan et al, 2013;Mantilla et al, 2014), traumatic brain injury (Aungst et al, 2013), motivated behaviour (Johnson et al, 2008), antidepressant drug signalling (Rantamäki et al, 2011), circadian rhythms (Girardet et al, 2013), retinal circuitry (Kaneko et al, 2008;Majumdar et al, 2011), tests of TrkB agonists (Jang et al, 2010;Choi et al, 2012), receptor sequestration (Mou et al, 2011), glucocorticoid receptor interaction (Arango-Lievano et al, 2015, and most recently, the interaction of RhoGTPase signalling (Hedrick et al, 2016). This body of research demonstrates that this transgenic line of mice is a valuable model for analyzing the influence of TrkB.FL receptor function.…”
Section: The Trkb F616a Mutant As a Model For Studying Bdnf Signallingmentioning
confidence: 99%